Development of Deep Learning-Based Ethnomathematics E-LKPD to Improve Mathematical Creative Thinking - Fitriyani; Kusno (Tsaqila | Jurnal Pendidikan dan Teknologi, 2026)
This study focuses on the development of ethnomathematics-based E-LKPD integrated with a deep learning approach as an effort to improve the mathematical creative thinking ability of ninth-grade students in the topic of transformation geometry. This study used a development method (R&D) with a 4D model which includes the stages of defining, designing, developing, and disseminating. The subjects of the study were ninth-grade students consisting of 17 students in the experimental class and 18 students in the control class at SMP Boarding School Putra Harapan Purwokerto. Data collection in this study was carried out using validation sheets from experts, student response questionnaires, as well as tests of mathematical creative thinking ability in the form of open-ended questions. The developed E-LKPD product was assessed to meet the criteria of being very valid and showed a very good level of practicality. The effectiveness analysis results indicate that the mathematical creative thinking ability of students in the experimental class differs significantly compared to the control class, with an effect size value falling into the medium category. The developed E-LKPD product shows feasibility for use as innovative teaching material that can strengthen meaningful learning and encourage the improvement of students' mathematical creative thinking abilities.